Carbon partitioning in eelgrass: regulation by photosynthesis and the response to daily light-dark cycles - Zimmerman, R.C. (University of California, Los Angeles, CA.); Kohrs, D.G; Steller, D.L; Alberte, R.S (Plant physiology (Bethesda), 1995)
Diel variations in rates of C export, sucrose-phosphate synthase (SPS) and sucrose synthase (SS) activity, and C reserves were investigated in Zostera marina L. (eelgrass) to elucidate the environmental regulation of sucrose formation and partitioning in this ecologically important species. Rates of C flux and SPS activity increased with leaf age, consistent with the ontogenic transition from sink to source status. Rates of C export and photosynthesis were low but quantitatively consistent with those of many terrestrial plant species. The Vmax activity of SPS approached that of maize, but substrate-limited rates were 20 to 25% of Vmax, indicating a large pool of inactive SPS. SPS was unresponsive to the day/night transition or to a 3-fold increase in photosynthesis generated by high [CO2] and showed little sensitivity to inorganic phosphate. Consequently, regulation of eelgrass SPS appeared similar to starch- rather than to sugar-accumulating species even though eelgrass accumulates sucrose. Leaf [sucrose] was constant and high throughout the diel cycle, which may contribute to the down-regulation of SPS. Root sucrose synthase activity was high but showed no response to nocturnal anoxia. Root [sucrose] also showed no diel cycle. The temporal stability of [sucrose] confers an ability for eelgrass to buffer the effects of prolonged light limitation that may be key to its survival and ecological success in environments subject to periods of extreme light limitation and chaotic daily variation in light availability